Pengembangan Usaha Mikro Kecil Menengah (UMKM) Melalui E-Commerce - Umratul Hasanatun; Nur Aini; Nurul Apriatun; Zihan Saputra; Sultan Salahudin; Abdul Muad; Aris Munandar (Journal of Management and Creative Business, 2024)
The aim of this research is to ascertain how to utilize electronic media, namely E-Commerce, for MSMEs in Ntobo Village to improve and develop business. The research used is descriptive research with a qualitative approach. The development of a woven business group uses initial capital with its own savings, innovates its production results, expands its marketing network, and completes its business facilities and infrastructure. Apart from that, facilitation from the Bima City Cooperatives and SMEs Department has given MSMEs access to capital sources, provided coaching and training, product promotion activities and expanded the marketing of woven products through E-Commerce. The development of MSMEs through e-Commerce is increasing because of the benefits that will be gained by MSMEs themselves, and can also make it easier for all groups to reach and access anywhere and anytime to carry out transactions via the internet.